Screening of undiagnosed depression among elderly primary care patients: a cross-sectional study from the Republic of Srpska, Bosnia and Herzegovina - Kosana Stanetić; Verica Petrović; Bojan Stanetić; Vesna Kević; Mirko Stanetić; Jelena Matović; Srebrenka Kusmuk; Maja Račić (Medicinski glasnik, 2019)
Aim: To examine the prevalence of undiagnosed depression among primary care elderly patients in the entity of the Republic of Srpska (Bosnia and Herzegovina) as well as the sociodemographic and clinical risk factors associated with depression. Methods: A cross-sectional study was conducted between April and June 2019 in nine towns of the Republic of Srpska. The study sample included 1,198 primary care patients older than 65 years of age. Research instruments included a sociodemographic questionnaire and Geriatric Depression Scale-Short Form (GDS-SF). Results: Positive screening test (GDS-SF score > 5), which indicates depression was found in 484 (40.4%) participants. Multivariate regression analysis showed that lower education levels [OR = 1.565, 95% CI (1.13-2.17)], divorced and widowed [OR = 1.366, 95% CI (1.16-1.62)], poor financial situation [OR = 1.690 , 95% CI (1.25-2.29)], non-home residents [OR = 2.200, 95% CI (1.41-3.44)], non-hobby patients [OR = 2.115, 95% CI (1.54-2.91) ], non-friends [OR = 3.881, 95% CI (2.70-5.57)], patients suffering from chronic pain [OR = 2.414, 95% CI (1.72-3.39)], patients with daily life limitation activities [OR = 1.415, 95% CI (1.03-1.95)], patients with three or more chronic diseases [OR = 1.593, 95% CI (1.12-2.27)], patients using five or more drugs [OR = 1.425. 95% CI (1.00-2.03)], and patients with history of previous depression [OR = 2.858, 95% CI (1.94-4.21)] were at higher risk for depression. Conclusion: The prevalence of undiagnosed depression in the elderly in Republic of Srpska is high. Future strategies are needed to strengthen screening of geriatric depression in primary health care.
Keywords: age; Bosnia and Herzegovina; depression; depressive disorder; primary health care; patients